Product Entitativity: How the Presence of Product Replicates Increases Perceived and Actual Product Efficacy - VanBergen, Noah; Irmak, Caglar; Sevilla, Julio (Journal of Consumer Research, 2020)
Abstract Many studies document the benefits of presenting smaller quantities of products, particularly when differences in quantity relate to availability or popularity. However, we know less about the effects of quantity differences in contexts unrelated to scarcity, such as when products are depicted in ads, special displays, or online retailing settings. The present research builds on extant literature by investigating a previously unexplored question: How do product perceptions differ depending on whether consumers view a single unit in isolation, versus as one unit among identical product replicates? Five experiments demonstrate that presenting multiple product replicates as a group (vs. presenting a single item) increases product efficacy perceptions because it leads consumers to perceive products as more homogeneous and unified around a shared goal. That is, consumers perceive greater product entitativity when viewing a group of product replicates. As a result, the perceived and actual ability of products to deliver that function (i.e., product efficacy) increases.